1987
DOI: 10.1128/mcb.7.9.3113
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and physical characterization of three essential conidiation genes from Aspergillus nidulans.

Abstract: We cloned and characterized three genes from Aspergillus nidulans, designated brUA, abaA, and wetA, whose activities are required to complete different stages of conidiophore development. Inactivation of these genes causes major abnormalities in conidiophore morphology and prevents expression of many unrelated, developmentally regulated genes, without affecting the expression of nonregulated genes. The three genes code for poly(A)+ RNAs that begin to accumulate at different times during conidiation. The briA-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
187
0
3

Year Published

1989
1989
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(199 citation statements)
references
References 18 publications
(10 reference statements)
8
187
0
3
Order By: Relevance
“…It has been demonstrated that transcription of ivoB is regulated, directly or indirectly, by brlA (Adams et al 1988;Birse & Clutterbuck, 1990 b). There is also good evidence that brlA encodes a DNA-binding protein; it has been sequenced and the inferred peptide contains a zincfinger DNA-binding motif (Boylan et al, 1987). Furthermore, mis-scheduled expression of brlA is sufficient to activate transcription of many genes characteristic of later conidiophore development, including ivoB (Adams et al, 1988).…”
Section: Genetics Of Aspergillus Conidiophore Pigment I737mentioning
confidence: 99%
“…It has been demonstrated that transcription of ivoB is regulated, directly or indirectly, by brlA (Adams et al 1988;Birse & Clutterbuck, 1990 b). There is also good evidence that brlA encodes a DNA-binding protein; it has been sequenced and the inferred peptide contains a zincfinger DNA-binding motif (Boylan et al, 1987). Furthermore, mis-scheduled expression of brlA is sufficient to activate transcription of many genes characteristic of later conidiophore development, including ivoB (Adams et al, 1988).…”
Section: Genetics Of Aspergillus Conidiophore Pigment I737mentioning
confidence: 99%
“…The deletion of sfgA causes hyperactive conidiation and eliminates the need for fluG in conidiation and ST production. These led us to propose that the developmental transition from vegetative growth in A. nidulans occurs via removal of the negative regulator SfgA, which inhibits precocious activation of brlA during proliferation, thereby allowing proper vegetative growth.During conidiogenesis, the spatial and temporal expression of brlA, abaA, and wetA is tightly controlled (Boylan et al 1987;Mirabito et al 1989;Adams et al 1998;Ni et al 2010). For instance, transcripts of brlA and abaA specifically accumulate during the early-to-middle phases of conidiophore formation and quickly disappear upon the formation of conidia.…”
mentioning
confidence: 99%
“…During conidiogenesis, the spatial and temporal expression of brlA, abaA, and wetA is tightly controlled (Boylan et al 1987;Mirabito et al 1989;Adams et al 1998;Ni et al 2010). For instance, transcripts of brlA and abaA specifically accumulate during the early-to-middle phases of conidiophore formation and quickly disappear upon the formation of conidia.…”
mentioning
confidence: 99%
“…The Aspergillus nidulans brlA gene, which is essential for conidiation, encodes a zinc finger protein. BRLA is directly involved in regulating the transcription of other developmentally related genes (Boylan et al 1987, Marshall and Timberlake 1991, Chang and Timberlake1993, Andrianopolus and Timberlake 1994, Adams et al 1998. The A39 sequence and brlA shared high similarity within the conserved domain of the zinc finger protein.…”
Section: Discussionmentioning
confidence: 99%